Analisis Efektivitas Metode ARIMA dalam Peramalan Nilai Tukar Berdasarkan Systematic Literature Review - Paloma Ransi; Abdul Rezha Efrat Najaf; Tri Luhur Indayanti Sugata (MDP Student Conference, 2026)
This study reviews the application of the Autoregressive Integrated Moving Average (ARIMA) method for exchange rate forecasting based on previous research. The review focuses on model characteristics, order selection, and forecasting accuracy. A Systematic Literature Review (SLR) was conducted on relevant articles published within the last five years. The findings indicate that ARIMA remains widely applied, particularly for short-term forecasting, with low-order models often providing the best performance. However, no single ARIMA model is universally applicable across different countries and conditions. The study concludes that ARIMA is effective as a baseline forecasting method but has limitations in capturing complex market dynamics.